Investigating individual differences with qualitative research methods: Results of a meta-analysis of leading applied linguistics journals - Albert, Ágnes; Csizér, Kata (Studies in Second Language Learning and Teaching, 2022)
The aim of the present article is to provide a systematic review of qualitative studies in the leading journals of our field focusing on their distributional properties in the various journals as well as topic choice and selected quality control issues. In order to achieve this aim, we carried out a systematic review of research articles published in leading journals in our field, namely, Applied Linguistics, Language Learning, Language Teaching Research, Studies in Second Language Acquisition and Modern Language Journal between 2016 and 2020. Our sample contains 93 articles in which researchers employed qualitative research methods or mixed methods including a qualitative component. Our main results indicate that there is great variation among journals in terms of the number of qualitative studies. As for topic considerations, some traditional individual difference variables seem to have a dominant role, with cognitive processes involved in language acquisition gaining some ground as well. Concerning quality control issues, there could be room for improvement with regard to reporting the quality control measures, including the tools employed in the studies. Based on our results, we can conclude that a more systematic understanding of acceptable processes in the field of applied linguistics could increase not only the number of qualitative articles published but also their topical importance.